Safety practices in the mechanical engineering workshop politeknik merlimau - Rahman, Noorasikin Abd; Basir, Ishak Mohamed (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
Safety is a crucial aspect that must be emphasized when performing tasks in the workshop. This is important to prevent accidents that can result in injuries or even loss of life. Knowledge, understanding, and practice of safety in the workshop are critical during machining and welding practical sessions. These practices need to be instilled in every student so that they become a culture when students carry out work in the machining and welding workshops. Therefore, this study was conducted to identify the level of knowledge, awareness, and acceptance of safety practices among students. The study location was the Machining and Welding Workshops in the Department of Mechanical Engineering (JKM), Politeknik Merlimau (PMM). The number of respondents involved was 170 students who conducted machining and welding practicals from the first to the fourth semester. A total of 21 questionnaire items were constructed to address each research question. Data were analyzed using the